2017
DOI: 10.1089/neu.2015.4339
|View full text |Cite
|
Sign up to set email alerts
|

Early and Persistent Dendritic Hypertrophy in the Basolateral Amygdala following Experimental Diffuse Traumatic Brain Injury

Abstract: In the pathophysiology of traumatic brain injury (TBI), the amygdala remains understudied, despite involvement in processing emotional and stressful stimuli associated with anxiety disorders, such as post-traumatic stress disorder (PTSD). Because the basolateral amygdala (BLA) integrates inputs from sensory and other limbic structures coordinating emotional learning and memory, injury-induced changes in circuitry may contribute to psychiatric sequelae of TBI. This study quantified temporal changes in dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 50 publications
5
43
2
Order By: Relevance
“…However, in accordance with previous results published for the BLA 20 , silver staining did not reveal any evidence of overt neuropathology. Analysis of astrocytosis revealed that in contrast to our previous work in the BLA, astrocytes were not activated in the CeA following dTBI 20 . This indicates that CeA microglial activation is independent of the presence of pathology and may play an alternative role in the sequalae of events after TBI 69 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, in accordance with previous results published for the BLA 20 , silver staining did not reveal any evidence of overt neuropathology. Analysis of astrocytosis revealed that in contrast to our previous work in the BLA, astrocytes were not activated in the CeA following dTBI 20 . This indicates that CeA microglial activation is independent of the presence of pathology and may play an alternative role in the sequalae of events after TBI 69 .…”
Section: Discussioncontrasting
confidence: 99%
“…No significant alterations were detected in the BLA in anesthetized rats in this study, although studies using focal TBI models indicate that BLA circuitry becomes weakened through altered neuronal excitability, changes in N-methyl-D-aspartate (NMDA) receptors, and changes to GABAergic production proteins (GAD-67), all of which may provide compensatory responses that primarily influence glutamate release in the CeA 20,64,65 . Previously, we reported increased neuropathology in the somatosensory cortex and thalamus following dTBI, which could also alter sensory input into the BLA 66,67 .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Additionally, there is increased surface expression and function of α 7 nAChRs, expressed on somatodendritic regions of BLA glutamatergic neurons (Klein & Yakel, ). Another recent study found enhanced dendritic branch intersections in BLA pyramidal and stellate neurons, although BLA was relatively free of neuropathology compared to other brain regions (Hoffman et al., ). Enhanced dendritic complexity would affect the regulation of BLA neurocircuitry—probably disrupting the normal processing and perception of fear‐related stimuli.…”
Section: Bla Nicotine and Nachrs In Acquired Anxiety Disordersmentioning
confidence: 96%
“…Vyas and colleagues (Vyas et al 2004) demonstrated that the dendritic hypertrophy in basolateral amygdala resulting from chronic immobilization (2 h/day, 10 days) persists up to 21 days after the cessation of stress. Likewise, stellate and pyramidal neurons in the basolateral amygdala neurons undergo dendritic hypertrophy in as little as one day after traumatic brain injury (which may perhaps be considered a physiological stressor), which persists at least four weeks later, despite lack of neuronal loss in this structure (Hoffman et al 2017). Note, however, that the effect of stress on the basolateral amygdala may depend on intensity or modality of the stressor: others have found that daily restraint stress (6 h/day, 10 days) resulted in significant debranching and retraction of pyramidal neurons in basolateral amygdala (Grillo et al 2015), as did acute elevated platform stress (Maroun et al 2013).…”
Section: Unanswered Questions and Future Directionsmentioning
confidence: 99%